Alarm Pada Clearance Executive Monitor Instrument Landing System (ILS) Glide Path 36 PERUM LPPNPI Kantor Cabang Manado - Octavianie, Adhitya; Ichsan, Muh. (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
ILS equipment is one of the landing navigational aids using radio waves as an instrument (non-visual) which is used by pilots in carrying out aircraft approach and landing procedures at an airport. The problem is the Instrument Landing System (ILS) on the Glide Path (GP) equipment on Runway 36. Glide Path has a monitor that functions to monitor the signal to be emitted by the antenna, the signal to be monitored is processed by the detector module, there are 3 detectors including COURSE CSB detector, COURSE SBO detector, and CLEARANCE detector. The signal coming from the antenna will be detected (sampled) by each detector and then forwarded to the monitor module for processing and the results are displayed on the PMDT (Portable Maintenance Data Terminal) monitor. When the value of the monitor reading exceeds the limit of the tolerance value that has been set, a pre-alarm / alarm will occur. The results obtained that the Clearance detector module on the panel box monitoring combining network connected to the monitor reading was damaged, so replacing the detector module and resetting the selectors on the panel box as well as calibrating and normalizing are the problem-solving steps.